Biocompatibility Of Electrospun Bombyx Mori Silk Fibroin With Poly(3-Hydroxybutyrate-Co-3-Hydroxyhexanoate) As A Biomaterial For Tissue-Engineered Scaffolds - Ang, Shaik Ling (2019)
Polyhydroxyalkanoates (PHAs) are polyesters produced by microorganisms under unbalanced growth conditions. They are well documented as a biodegradable and biocompatible polymer, making them attractive as biomaterials for applications in tissue engineering. Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) P(3HB-co-3HHx) is one of the members of the PHA family that has shown superior mechanical properties and processability compared to poly(3-hydroxybutyrate) [P(3HB)] and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [(P(3HB-co-3HV)]. However, the biocompatibility of P(3HB-co-3HHx) is still inadequate because of its hydrophobic properties that has hampered its direct use as scaffold material. In this study, silk fibroin (SF) derived from Bombyx mori cocoons, which is a widely used and studied protein polymer for biomaterial applications have been used to improve the cell affinity and biocompatibility of P(3HB-co-3HHx).